Exploration of Ethnobotanical Values in Mandar Community Wedding and Seven-Month Ceremonies for the Development of Biology Learning Resources - Handayani, Tiara; Ramlah; Fausan, Muhammad Mifta; Muis, Nurmuliayanti; Yusrianto Nasir (Universitas Sulawesi Barat, 2026)
The Mandar tribe of West Sulawesi maintains well-preserved cultural traditions, including the ritualized use of diverse plant species imbued with symbolic values (ussul) and local ecological knowledge. This study aimed to: (1) identify plant species utilized in the wedding and seven-month ceremonies of the Mandar people in Majene Regency; (2) analyze the symbolic significance (ussul) of each plant from the Mandar cultural perspective based on the Relative Frequency of Citation (RFC) index; and (3) develop an ethnobotanical e-catalog using the ADDIE model as a biology learning resource on biodiversity for Grade X senior high school students. A descriptive qualitative approach was employed, with data collected through semi-structured interviews, direct observation, and documentation involving 21 key informants (customary leaders, traditional shamans, and community members) in the Mangge and Kalasa neighborhoods of Totoli Village, Banggae District, Majene Regency, from April to July 2025. Plant identification was conducted using PlantNet, Plants of the World Online (POWO), and Plantamor. Results revealed 21 species from 16 families in the wedding ceremony and 9 species from 8 families in the seven-month ceremony, predominantly herbs and trees. Seven species recorded the highest RFC values (RFC = 1.00): Cocos nucifera, Piper betle, Areca catechu, Curcuma longa, Oryza sativa, Musa sp., and Eragrostis tenella, each bearing distinct ussul reflecting the philosophy of Mandar life. The findings were compiled into an e-catalog developed through the Analysis, Design, and Development stages of the ADDIE model, validated as highly valid (M = 4.62 out of 5.0) by subject-matter and cultural experts, and deemed suitable as a biology learning resource on biodiversity.